Part 2: Theoretical Intakes of Modern-Day Paleo Diets. Issue 4 (July 2021) - Karlsen, Micaela C.; Livingston, Kara A.; Agoulnik, Dasha; Miki, Akari; Lichtenstein, Alice H.; Gilhooly, Cheryl H.; Folta, Sara C.; Economos, Christina D.; McKeown, Nicola M.
Abstract : Background: The Paleo diet is a popular dietary pattern based on interpretation of evolutionary diets. Objective: The aim of this study was to assess the relative dietary quality of theoretical, modern-day Paleo meal plans, in comparison with national nutrition guidance. Methods: This analysis used data from the Adhering to Dietary Approaches for Personal Taste survey. Survey respondents who self-identified as following a Paleo diet (N = 925) reported their top sources of food and nutrition information, and a random sample (n = 200) were selected for analysis. Five days of theoretical meal plans identified from each of the top 6 sources cited by Paleo participants (for a total of 30 days of meal plans) as well as 21 days of theoretical MyPlate meal plans, were analyzed using the Nutrition Data System for Research. Food and nutrient levels of Paleo meal plans were compared with the Dietary References Intakes and MyPlate meal plans. Results: Paleo meal plans contain no identifiable refined grains or added sugars and have higher fruit and vegetable intakes than MyPlate meal plans. However, Paleo meal plans exceeded recommended levels of saturated fat (19% kcal/day), resulting in low unsaturated-saturated fat ratios, and did not meet the Dietary References Intakes for total carbohydrate, fiber, calcium, and potassium. Conclusion: Although certain aspects of promoted Paleo meal plans offer improvements over typical American intakes, Paleo diets should be approached with caution, particularly because of the potential for increased cardiovascular risk owing to low unsaturated/saturated fat ratios. Future research should compare actual intakes with theoretical targets.